Improvement of Interest And Learning Results of Science with Problem Based Learning Model in SD Negeri Keteleng 02 - Fera Setiyadi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to increase the interest and learning outcomes of students in the science muple in grade IV elementary schools with the Problem Based Learning (PBM) learning model. The research conducted was a Classroom Action Research (CAR) in three cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In cycle I students who completed after carrying out the post test were 74%. In cycle II participants students who complete after carrying out the post test are 100%. These results indicate that the Problem Based Learning (PBM) learning model can improve student learning outcomes, especially Class IV science muple at SDN Keteleng 02.